Crystalline to amorphous transformation in solid-solution alloy nanoparticles induced by boron doping. Issue 85 (25th September 2020) - Kobayashi, Keigo; Kusada, Kohei; Wu, Dongshuang; Ogiwara, Naoki; Kobayashi, Hirokazu; Haruta, Mitsutaka; Kurata, Hiroki; Hiroi, Satoshi; Seo, Okkyun; Song, Chulho; Chen, Yanna; Kim, Jaemyung; et al.
Abstract : Synthesis of Pd–Ru–B solid-solution alloy is first reported. Alloying of B atoms into Pd–Ru alloy is accompanied by a characteristic crystalline–amorphous transformation to results in the disappearance of long-range atomic correlation. Abstract : We synthesized a palladium–ruthenium–boron (Pd–Ru–B) solid-solution ternary alloy. Elemental mappings confirmed successful alloying of B with Pd–Ru body without changing the particle sizes, demonstrating the first discovery of this ternary alloy. Pair distribution function analysis revealed a drastic decrease in atomic correlation in Pd–Ru nanoparticles by B doping. This result gives the first example of structural transformation from crystalline to amorphous in solid-solution alloy nanoparticles induced by the doping of light elements.